The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/tafs.10058
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Movements of Postcopulatory Female Blue Crabs Callinectes sapidus in Tidal and Nontidal Estuaries of North Carolina

Abstract: For migratory species, understanding the timing, direction, and mechanism of migration is critical for successful fisheries management. We investigated migratory movements of postcopulatory female blue crabs Callinectes sapidus in three estuaries with different tidal regimes in North Carolina using a mark–recapture study. All crabs tagged were within about 2 weeks of the terminal molt to maturity (mating generally takes place immediately after the molt). In general, distances traveled (mean ± SE = 6.8 ± 0.6 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Similarly, tagged crabs in a study by Aguilar et al (2005) showed no directed down‐bay movements until the fall months (September–November). Darnell and Kemberling (2018), however, tagged postcopulatory female blue crabs that were within 2 weeks of their terminal molt and released in three rivers of southeastern North Carolina. They found slow and sustained seaward migration prior to oviposition in summer and fall, which is consistent with the more predominant pattern we observed in 2008 at all sites and in 2009 at all but two sites.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, tagged crabs in a study by Aguilar et al (2005) showed no directed down‐bay movements until the fall months (September–November). Darnell and Kemberling (2018), however, tagged postcopulatory female blue crabs that were within 2 weeks of their terminal molt and released in three rivers of southeastern North Carolina. They found slow and sustained seaward migration prior to oviposition in summer and fall, which is consistent with the more predominant pattern we observed in 2008 at all sites and in 2009 at all but two sites.…”
Section: Discussionmentioning
confidence: 99%
“…Tags were attached externally by 0.26–0.35‐mm‐diameter annealed 316 stainless steel wire wrapped around the lateral spines (Figure 1). This is a tagging method commonly used for blue crabs that does not impact survival and has a low rate of tag loss (Aguilar et al 2005; Medici et al 2006; Darnell and Kemberling 2018). Tag loss probability has been estimated to be 0.00067/day (Corrick 2018, based on Hines et al unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that estuarine portunids perform larval export, which begins with female spawning at the mouth of the estuaries [123][124][125], and after hatching, as observed in Callinectes sapidus Rathbun, 1896, the zoea I larvae that have strong negative geotaxis [126], remain in the upper two meters of the water column to take advantage of the bay/estuary outflow currents, which, driven by the wind, head towards the continental shelf [79,106]. These larval patches move along with the plume edge, and after a few days drifting on the continental shelf, they move from the plume edge to the open sea [80], remaining in superficial waters during the entire larval development period [79,127,128].…”
Section: Portunidaementioning
confidence: 99%